2002
DOI: 10.1021/la020312a
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of Ag/Au(111) Expanded Structures

Abstract: In this work, we present a series of first-principles calculations on the stability of expanded silver monolayers adsorbed on a gold (111) substrate. The main result obtained is that none of the structures that are more expanded than the (1 × 1) compact monolayer is more stable than the bulk silver phase and hence should not be underpotentially deposited. A possible explanation for the discrepancy between experimental and theoretical results may lie in the strong work function shift generated by the adsorbate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In contrast, the electrodeposition of less than 1 monolayer of Ag onto the Au(111) surface produces open structures, as previously shown. However, a series of first-principle calculations by Sanchez et al. showed that no structure more expanded than a (1 × 1) compact monolayer is more stable than a bulk Ag deposit and hence UPD of Ag should not occur on Au(111) . In order to explain the discrepancy between the calculations and the experimental results, it was suggested that adsorbed Ag may generate a large shift in the work function thus inducing a negative shift in the potential of zero charge ( pzc ) and resulting in the additional adsorption of anions and a change in the Au–Ag binding energy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, the electrodeposition of less than 1 monolayer of Ag onto the Au(111) surface produces open structures, as previously shown. However, a series of first-principle calculations by Sanchez et al. showed that no structure more expanded than a (1 × 1) compact monolayer is more stable than a bulk Ag deposit and hence UPD of Ag should not occur on Au(111) . In order to explain the discrepancy between the calculations and the experimental results, it was suggested that adsorbed Ag may generate a large shift in the work function thus inducing a negative shift in the potential of zero charge ( pzc ) and resulting in the additional adsorption of anions and a change in the Au–Ag binding energy.…”
Section: Discussionmentioning
confidence: 93%
“…35−40 However, a series of first-principle calculations by Sanchez et al showed that no structure more expanded than a (1 × 1) compact monolayer is more stable than a bulk Ag deposit and hence UPD of Ag should not occur on Au(111). 41 In order to explain the discrepancy between the calculations and the experimental results, it was suggested that adsorbed Ag may generate a large shift in the work function thus inducing a negative shift in the potential of zero charge (pzc) and resulting in the additional adsorption of anions and a change in the Au−Ag binding energy. The open structures observed during the electrodeposition of Ag onto Au(111) are dependent on the anion present; for example, in the presence of sulfate, the Ag UPD overlayer exhibits a (3 × 3) structure, in the presence of nitrate, a (4 × 4) structure, and in pure perchlorate electrolyte, another open structure.…”
Section: Discussionmentioning
confidence: 99%
“…5, the underpotential shift ΔE upd defined at the beginning of this chapter can be estimated from two calculations: the binding energy of the adsorbate M to the substrate S and the cohesive energy of bulk M. This is a good approximation for compact adsorbates and in those cases where the work function difference between bulk M and bulk S is small. In the first case, this so because in the case of compact upd adsorbates, adatoms present a larger depolarization [199], so that solvation effects should be smaller and may be neglected. Figure 3.27 shows effective dipole moments of Ag atoms adsorbed on …”
Section: ð3:54þmentioning
confidence: 99%
“…8 First principles density functional theory (DFT) has been applied to obtain atomistic insights into the stability and structure of the metal monolayers achieving varying degrees of correspondence with experimental voltammetry. [9][10][11][12][13][14][15] These calculations are typically performed in the absence of a solvent; however, key features of the interface such as anion co-adsorption have been included when warranted, leading to enhanced descriptions of the interface. 14,15 Entropic effects have additionally been considered to obtain surface chemical potentials by including ideal configurational entropy or by fitting an Ising-like Hamiltonian to DFT results and subsequently performing grand canonical Monte Carlo calculations.…”
Section: Introductionmentioning
confidence: 99%